Literature Review On English Consonant Pronunciation Problems Encountered By Indonesian Students - Fadiah Nur Amalia; Susi Sahmarito Rambe; Yani Lubis (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Because the ultimate goal of English instruction is for students to be able to communicate successfully in English, it is critical for EFL students to have a clear and comprehensible pronunciation of the language. As a result, English students must place a higher focus on their ability to accurately enunciate words. Learning good pronunciation is one of the most important things one can do to improve one's communication skills. However, many English as a foreign language students find it difficult to polish their pronunciation. Outside of Indonesia, students in Indonesia are required to study English as their first language. Students study English at school solely for the purpose of communication. As a result, they are unable to correctly enunciate any English word, despite the fact that they are expected to utilize English fluently outside of the classroom. The objective of this essay is to analyze the obstacles and reasons that Indonesian students have when attempting to accurately pronounce English consonants by analyzing past research. Following an examination of the study, it was discovered that Indonesian students had similar difficulty and inaccuracies in pronouncing English consonants. The first reason is because some consonants in English do not exist in Indo-European or their native language. This is due to the fact that English consonants were taken from other languages. The second issue is that most Indo-European students have difficulty pronouncing stop consonants such as / v / θ / ð / ʃ / ʒ / tʃ / and / dʒ /. These are the vowels and consonants that come at the end of words. The difficulties distinguishing between voiced (consonants with vibration) and voiceless (consonants without vibration) consonants, the inconsistent sounds for vowel letters in English and Bahasa Indonesia, vowel-letter combinations, silent letters, a lack of knowledge of English fricative sounds, a preference for speaking their mother tongue rather than English, a lack of experience correctly pronouncing things, and the sounds of two or three combinations of consonants.